Synthesis and Use of Complex Titanium-Containing Coagulant in Water Purification Processes - Evgenii Kuzin (Inorganics)
Titanium-containing coagulants are a new development in physical and chemical water purification processes. Despite their high efficiency and the absence of the drawbacks that are typical of traditional reagents, the high cost of titanium compounds restrains their extensive implementation. As part of this work, a concept technology for the synthesis of complex titanium-containing reagents using chemical dehydration processes was proposed. It was found that the composition of a complex titanium-containing coagulant consists of a mixture of aluminum sulfate 50–87 wt.%, aluminum chloride 10–40 wt.%, and titanium oxysulfate 2.5–10.0 wt.%. It was ascertained that the optimal content of the modifying additive in titanium compounds is 5.0–7.5 wt.%. The comparison of the coagulation efficiency of traditional aluminum- and iron-containing reagents and freshly synthesized reagents showed that the use of complex titanium-containing coagulants allows us not only to minimize the residual concentrations of various pollutants (phosphates, turbidity, oxidizable organic compounds) but also to reduce the reagent consumption by 20–25%, as well as to intensify the processes of sedimentation and filtration of coagulation sludge. Based on the data set obtained, the prospects for the production and use of complex titanium-containing coagulants for natural and wastewater of different origins are proven.